Lentogenic avian paramyxovirus 1 of both class I and class II are circulating in danish wild and commercial waterfowl - Karen Martiny; Yuan Liang; Pia Ryt-Hansen; Lars E. Larsen; Jens P. Christensen; Charlotte K. Hjulsager (npj Viruses)
Abstract Newcastle disease, a notifiable avian disease, is caused by virulent avian paramyxovirus 1 (APMV-1). In this study, we screened samples collected through the active and passive surveillance for avian influenza virus in Denmark between 2014 and 2022 for APMV-1, detecting 32 APMV-1 in wild and commercial waterfowl. Phylogenetic analysis identified them as class I genotype 1.2 and class II genotype I.2 viruses, all with monobasic fusion (F) cleavage sites (112ERQERL117 and 112GKQGRL117), characterizing them as lentogenic. Nucleotide and amino acid similarities ranged from 95 to 99.8% and 98.2 to 100% for class I viruses and 95.6–99.8% and 98.7–100% for class II viruses. Genetic comparisons of F genes showed divergence from vaccine strains, ruling out vaccine spillover. Selection analysis revealed neutral and negative selection pressures, suggesting limited adaptive evolution. These findings indicate that lentogenic APMV-1 circulated in Denmark from 2014 to 2022 without strong selection pressures driving significant genetic changes.